2021
DOI: 10.1002/cphc.202000978
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐projected QM/MM Free Energy Simulations for Oxidation Reaction of Guanine in B−DNA by Singlet Oxygen

Abstract: Guanine is the most susceptible base to oxidation damage induced by reactive oxygen species including singlet oxygen (1O2, 1Δg). We clarify whether the first step of guanine oxidation in B−DNA proceeds via either a zwitterionic or a diradical intermediate. The free energy profiles are calculated by means of a combined quantum mechanical and molecular mechanical (QM/MM) method coupled with the adaptive biasing force (ABF) method. To describe the open‐shell electronic structure of 1O2 correctly, the broken‐symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…It is mostly related to the energy calculations of the 1 O 2 reactant and the precursor complex. To obtain accurate PES, the Yamaguchi’s approximate spin projection was adopted to correct for spin contamination in 1 O 2 and in the precursor complex. Note that the late-stage complexes and TSs are dominated by single electronic states, thus spin contamination is no longer a serious issue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mostly related to the energy calculations of the 1 O 2 reactant and the precursor complex. To obtain accurate PES, the Yamaguchi’s approximate spin projection was adopted to correct for spin contamination in 1 O 2 and in the precursor complex. Note that the late-stage complexes and TSs are dominated by single electronic states, thus spin contamination is no longer a serious issue.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic structure of 1 O 2 computed with broken-symmetry DFT is inherently an equal mixture of singlet 1 O 2 (↑↓, S = 0) and triplet 3 O 2 (↑↑, S = 0). Previous computational studies revealed that the effect of spin contamination from the triplet state causes an error of more than 0.4 eV in the energy of 1 O 2 . It can be anticipated that spin contamination would affect the reaction PES of 1 O 2 with the radical cation of 8BrG •+ (↑, S = 1/2). Specifically, the target doublet state [ 1 O 2 (↑↓) -···8BrG •+ (↑)] in a reactant precursor complex may suffer from an energetically lower-lying quartet state [ 3 O 2 (↑↑) -···8BrG •+ (↑)].…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Classical molecular dynamics simulations were performed considering calculation parameters based on preparation instructions. 64 Next, docking calculations were conducted to search the complex formation between the Cas12a protein and guide RNA (binary system), followed for the Cas12a/gRNA complex and target DNA (ternary system). The Visual Molecular Dynamics (VMD) package was used to investigate the docking results.…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of the reaction PES for a radical with 1 O 2 is challenged by multi-configuration wavefunctions originating from the mixed open- and closed-shell character of 1 O 2 . The spin-restricted DFT cannot describe the static correlation arising from the two degenerate π* orbitals and overestimates the 1 O 2 excitation energy by 0.7 eV, whereas the unrestricted broken spin-symmetry DFT brings about spin contamination from 3 O 2 and underestimates the excitation by 0.5 eV. This problem affects not only the 1 O 2 reactant but also the intermediates and TSs for 1 O 2 addition to the guanine radical. ,, In the latter case, the target doublet state 2 [[9MG·1MC] •+ (↑)··· 1 O 2 (↑↓)] not only suffers from spin contamination of a lower-energy lying quartet state 4 [[9MG·1MC] •+ (↑)··· 3 O 2 (↑↑)] but also mistakenly converges to a lower-energy but incorrect doublet state 2 [[9MG·1MC] •+ (↓)··· 3 O 2 (↑↑)].…”
Section: Computational Analysismentioning
confidence: 99%